A Flexible and Boron-Doped Carbon Nanotube Film for High-Performance Li Storage - Wang, Lei; Guo, Wenlei; Lu, Pengyi; Zhang, Tao; Hou, Feng; Liang, Ji (Frontiers in Chemistry, 2019)
Boron-doped carbon nanotubes are a promising candidate for Li storage due to the unique electronic structure and high crystallinity brought by the boron dopants. However, the relatively low Li storage capacity has limited its application in the electrochemical energy storage field, which is mainly caused by the predominantly intact graphitic structure on their surface with limited access points for Li ion entering. Herein, we report a novel B-doped CNTs (py-B-CNTs) film, in which the CNTs possess intrinsically rough surface but flat internal graphitic structure. When used as a flexible anode material for LIBs, this py-B-CNTs film delivers significantly enhanced capacity than the conventional B-doped CNTs or the pristine CNTs films, with good rate capability and excellent cycling performance as well. Moreover, this flexible film also possesses excellent mechanical flexibility, making it capable of being used in a prototype flexible LIB with stable power output upon various bending states.